2004
DOI: 10.1080/09286580490514540
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and functional status from the 1995 National Health Interview Survey on Disability

Abstract: Vision had an impact on all ADLs and IADLs evaluated, with greater impact on self-reported function for younger adults. This suggests that younger adults perceive limitations associated with visual disability differently than do older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…Low vision and blindness have been very important public health problems worldwide. [1] In 1999, the World Health Organization proposed “Vision 2020: The Right to Sight” which has contributed to a reduction in the number of cases of blindness in the world. [2] Previous report by The Vision Loss Expert Group of the Global Burden of Disease Study showed that the prevalence of visual impairment was about 10% in adults aged 50 years or older in China.…”
Section: Introductionmentioning
confidence: 99%
“…Low vision and blindness have been very important public health problems worldwide. [1] In 1999, the World Health Organization proposed “Vision 2020: The Right to Sight” which has contributed to a reduction in the number of cases of blindness in the world. [2] Previous report by The Vision Loss Expert Group of the Global Burden of Disease Study showed that the prevalence of visual impairment was about 10% in adults aged 50 years or older in China.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Individuals with impaired vision may be at increased risk of injuries 3,4 and are more likely to curtail or stop driving. 5,6 Visually impaired elderly persons are at increased risk of falls and fractures [7][8][9][10] and depression.…”
mentioning
confidence: 99%
“…This agrees with two previous studies reporting an association between self-reported visual function and IADL limitations. 26,27 However, results concerning ADL tasks have been inconsistent. 26,27 Mobility limitations (a timed 4-m walk test and chair test) have been reported to increase significantly already in the early stage of decreasing VA even though more than half of the subjects had unaffected mobility functions until VA decreased to the level of ≤ 0.2.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Planning adequate measures to alleviate the influence of visual impairment on general disability requires more detailed information to show which functions are particularly prone to the effects of worsening VA. To our knowledge, only few previous studies, based on self-reported visual function, have analyzed the association between visual function and difficulties in separate ADL and IADL tasks. [26][27][28] We examined the effect of decreased self-reported and performance-based vision on functioning in a large nationally representative population-based study of people aged 55 years and above. We also analyzed which specific tasks, including self-reported and performance-based functions, are limited at various levels of visual acuity.…”
Section: Introductionmentioning
confidence: 99%